Clinical course and prognosis of acute post-streptococcal glomerulonephritis in children: A single-center experience - İsa Yılmaz; Mustafa Soran; Emre Leventoğlu (Turkish Journal of Pediatric Disease, 2026)
Objective: This study aimed to evaluate the impact of clinical and laboratory findings at presentation on renal function and their predictive value for long-term complications in children diagnosed with acute post-streptococcal glomerulonephritis (APSGN). Materials and Methods: Retrospective data of 37 APSGN patients aged 2–18 years, who were followed at the Konya City Hospital Pediatric Nephrology Clinic between January 2023 and January 2026, were analyzed. Clinical symptoms, laboratory parameters, ultrasonography findings, and treatment details were recorded. Results: Macroscopic hematuria was present in 73% of the patients and edema in 27%; approximately 70% of cases presented during the autumn and winter seasons. Patients who developed acute kidney injury (AKI) had significantly higher levels of C-reactive protein (CRP), anti-streptolysin O (ASO) and uric acid (p=0.004, p=0.025 and p=0.035, respectively). Increased renal parenchymal echogenicity on urinary system ultrasonography was observed in all patients with AKI (p=0.012). Hemoglobin levels were significantly lower in patients with nephrotic-range proteinuria (p=0.015). A total of 70.3% of the patients required hospitalization with a mean length of stay of 7.5±3.0 days. During follow-up renal function returned to normal in all patients and proteinuria regressed to normal levels in the majority of patients. Conclusion: Elevated inflammatory markers (CRP, ASO), high uric acid levels and increased renal parenchymal echogenicity are valuable early indicators of AKI in APSGN. Careful assessment of these non-invasive parameters at presentation is crucial for the early identification of high-risk patients and for guiding the management of potential complications.